COVID-19 response strategies: considering inequalities between and within countries - Lincoln Leehang Lau; Natalee Hung; Kendall Wilson (BMC, 2020)
Abstract Globally, the COVID-19 pandemic has been uncharted territory, and countries and governments have faced the challenge of implementing response strategies to manage local transmission. High-income settings have the resources to devote significant resources to testing, isolation, and contact tracing. Lower-income settings are pressured to emulate such initiatives, but often lack the resources and infrastructure to do so. We highlight the impact of these between-country inequalities, the within-country inequalities, and the potential magnification of unintended consequences due to COVID-19 control measures.